Study on the Operation Efficiency of Toll Roads in China from the Perspective of Scale Economy - Yan Xu; Jianqiang Fan; Haicheng Xu (Journal of Advanced Transportation)
Although China’s toll highways are world-renowned, they suffer from indisputable operational inefficiencies. Operationally, China’s toll highway sector is characterized by an administrative monopoly. In particular, governmental loan-repayment highways have such characteristics as franchising, monopoly, and “one highway by one company.” Hence, this study concentrates on the relationship between economic performance, administrative monopoly, and scale efficiency with respect to toll highways, and explores how the China-specific administrative monopoly affects the transformation of toll highways from scale to efficiency. Using the globally referenced data envelopment analysis- (DEA-) Malmquist Index, this study first measures the operational efficiency of China’s toll highway sector from 2010 to 2017. Based on provincial panel data, this paper then discusses the relationship between toll highway scale and economic performance through system-generalized method of moments estimation and verifies the status quo of the transformation of toll highways from scale to efficiency. From the provincial and industrial perspectives, this study further verifies how an administrative monopoly restricts the transformation from scale to total factor productivity and scale efficiency through the unique operation pattern in the toll highway sector. Finally, this study conducts an extended analysis of the relationship between operational efficiency and debt in the toll highway sector. The administrative monopoly is found to increase the debt burden of the toll highway sector and to have a negative impact on the long-term sustainability of the sector.